Situation Report: Romania, 14 October 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Contradictory Reports on Romanian Participation in Warsaw Pact Maneuvers Ceausescu Arrives in New York Half-yearly Economic Balance Sheet Department of Religious Cults Reorganized First International Fair in Bucharest Opens Party Contacts